1989
DOI: 10.1155/1990/16952
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Rat Thymic Epithelium Defined by Monoclonal Anticytokeratin Antibodies

Abstract: Ontogenetic study on the expression of cytokeratin (CK) polypeptides within particular subsets of rat thymic epithelial cells (TEC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Moreover, immunocytochemical studies have also demonstrated the phenotypical diversity of epithelial cells of the murine, human and rat thymus (van Vliet et al 1984;De Maagd et al 1985;Kampinga et al 1987). Especially notable are the data obtained using the anti-cytokeratin monoclonal antibodies, which demonstrated that there are several different subsets of medullary epithelial cells 1990;Milićević et al 1992). Likewise, various monoclonal antibodies to the medullary epithelial subset react with only some of these cells (Jambon et al 1981;Savino et al 1982;Gaudecker et al 1986;Farr and Anderson 1985;Rouse et al 1988) and, in accordance with our findings, also demonstrate their heterogeneity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, immunocytochemical studies have also demonstrated the phenotypical diversity of epithelial cells of the murine, human and rat thymus (van Vliet et al 1984;De Maagd et al 1985;Kampinga et al 1987). Especially notable are the data obtained using the anti-cytokeratin monoclonal antibodies, which demonstrated that there are several different subsets of medullary epithelial cells 1990;Milićević et al 1992). Likewise, various monoclonal antibodies to the medullary epithelial subset react with only some of these cells (Jambon et al 1981;Savino et al 1982;Gaudecker et al 1986;Farr and Anderson 1985;Rouse et al 1988) and, in accordance with our findings, also demonstrate their heterogeneity.…”
Section: Discussionsupporting
confidence: 89%
“…Their findings were confirmed by Gaudecker (1991). However, using anti-cytokeratin antibodies it is possible to distinguish additional subsets of thymic epithelial cells: in the medulla there are more than just two , 1990Milićević et al 1992). Light-microscopic immunophenotyping, using different monoclonal antibodies, has also documented the heterogeneity of epithelial cells in mouse, human and rat thymus, distinguishing between subcapsular, cortical and medullary areas (van Vliet et al 1984;De Maagd et al 1985;Kampinga et al 1987).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The cortical region directly under the capsule is called the subcapsular zone (SCZ), where proliferating DN thymocytes are localized ( 25 ). The SCZ contains a unique type of TECs ( 26 , 27 ), but their function has been poorly elucidated. The cortex of the adult mouse thymus contains a network of cTECs (estimated as comprising ~10 6 cells per mouse) that houses densely packed DP thymocytes (more than 10 8 cells per mouse) ( 28 ).…”
Section: Overview Of Thymic Stromal Cellsmentioning
confidence: 99%
“…The subcapsular/subtrabecular TECs link K1, K7, and K19 monoclonal anti-keratin antibodies, bound in a subcapsular/subtrabecular flat layer [72]. This subset of TECs has positive immunoreactivity for tyrosine hydroxylase (TH), α 1 -adrenoceptor (α 1 -AR) (both for TECs and the macrophages subcapsular/subtrabecular located), calcitonin gene-related peptide (CGRP), and bombesin [73,74].…”
Section: Thymic Epithelial Cells (Tecs)mentioning
confidence: 99%